The enigmatic role and development of the clavicle. Issue 3 (June 2016) - Ferguson, D.; Scott, B.
Abstract: The clavicle is a particularly odd bone with regard to its unique embryological development and the specific disease processes that it may encounter. The aim of this review is to describe the normal and abnormal development of the clavicle from its embryological origins until skeletal maturity. The review also attempts to account for the purpose of the clavicle by describing its structure and function.